The efficiency and safety in the implementation of physical exercise protocols as a non-drug treatment for chronic renal patients on hemodialysis and the difficulties of implementation in clinical practice: an integrative review (Research, Society and Development, 2021)
Chronic kidney disease (CKD) is a progressive kidney injury with a decreased glomerular filtration rate for more than three months. in its more advanced stage, it is called end-stage chronic renal failure. At this stage, patients are indicated for renal replacement therapy (RRT) or kidney transplantation. CKD brings with it several comorbidities such as anemia, chronic inflammatory state, hypertension, diabetes, chronic uremia. The anti-inflammatory role of regular physical exercise is closely correlated with the decrease in the progression of CKD and also with the patients' prognosis. This study aims to establish the effects and safety of regular physical exercise on the prognosis of patients with chronic kidney disease. This is an integrative review that used the consultation in the SCIELO, PUBMED and LILACS electronic databases, in September 2021, using the following previous criteria: publication date from January 1, 2016 to September 30, 2021; English language; descriptors included in the title and/or abstract – exercise (exercise), hemodialysis (haemodialysis) and chronic kidney disease (chronic kidney disease), free text, and only randomized clinical trials should be selected. The results showed a significant improvement in the modulation of inflammatory biomarkers, Kt/V, muscle strength, cardiorespiratory reserve, sleep pattern and health-promoting behaviors. Based on the results of this study, the intradialytic PE program proved to be efficient and feasible to apply. Even low-intensity exercise, even passively, had positive impacts on the quality of life and health of these individuals.